PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN DIVIDEN, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Riza Bernandhi; Dul Muid (Diponegoro Journal of Accounting, 2014)
This study aims to look at the factors that can affect the value of the company . This study is a replication of a previous study belongs Borolla ( 2011) . In Borolla research ( 2011) , the independent variables studied are managerial and institutional ownership structure . Differences in this study with previous studies is the addition of another independent variable that allegedly helped influence the value of the company dividend policy , leverage , and firm size. The population in this study are all companies listed on the Indonesia Stock Exchange ( BEI ) in 2010-2012 . Sampling is done by using purposive sampling and analytical methods used is multiple regression analysis . The results showed that the value of the company is not affected by the structure of managerial ownership , institutional ownership and dividend policy . Enterprise value is more influenced by the leverage factor and the size of the company . The implications of this research enterprise must consider the factors which make the enrichment is more interested investors to invest in a company that values the company can be improved